2018
DOI: 10.1111/add.14370
|View full text |Cite
|
Sign up to set email alerts
|

After how many drinks does someone experience acute consequences—determining thresholds for binge drinking based on two event‐level studies

Abstract: Event-level data collection techniques appear particularly suitable to estimate thresholds at which acute alcohol-related consequences occur. Binge drinking thresholds of 4+/5+ (women/men) drinks, equivalent to 40+/50+ g pure alcohol, predict the occurrence of consequences accurately in general but are too low to predict severe acute alcohol-related consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Our findings with youth and young adults align with similar research that suggests not all binge drinkers consume alcohol in the same pattern, endure drunkenness in the same manner, or experience similar consequences (Hingson and Zha, ; Read et al., ). These results are supported by event‐level assessment of alcohol use that found 4+/5+ binge drinking thresholds are accurate to predict some alcohol consequences, but were too low to predict severe acute consequences, such as blackouts and risky sex (Labhart et al., ). Consequently, use of a single level of risky drinking masks important information about higher, more dangerous consumption levels that should be a focus of public health prevention efforts.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings with youth and young adults align with similar research that suggests not all binge drinkers consume alcohol in the same pattern, endure drunkenness in the same manner, or experience similar consequences (Hingson and Zha, ; Read et al., ). These results are supported by event‐level assessment of alcohol use that found 4+/5+ binge drinking thresholds are accurate to predict some alcohol consequences, but were too low to predict severe acute consequences, such as blackouts and risky sex (Labhart et al., ). Consequently, use of a single level of risky drinking masks important information about higher, more dangerous consumption levels that should be a focus of public health prevention efforts.…”
Section: Discussionmentioning
confidence: 74%
“…Few studies provide data on how drinking influences blackouts at the event (vs. person) level. One study found that the average drinks consumed on blackout nights ranged from 7 to 11 (vs. 2 to 3 on nights without blackouts) among women and 10 to 20 (vs. 3 to 4 on nights without blackouts) among men (Labhart et al., ). “High‐intensity drinking” (HID), in particular, defined as twice the traditional “binge” or HED level of 4+/5+, has been shown to be associated with negative alcohol consequences (Hingson et al., ; Linden‐Carmichael et al., ).…”
Section: The Present Studymentioning
confidence: 99%
“…A MAC of less than or equal to 22 cm and TSFT<10 mm were considered to be a significant decrease . Binge drinking was defined as >5 standard drinks (>50 g) on one occasion . The stringent recording of dietary intake, alcohol intake, and anthropometric measurements was performed by the investigator (a gastroenterologist) in the presence of a dietician using standard diet charts.…”
Section: Methodsmentioning
confidence: 99%